2023
DOI: 10.3389/fphar.2023.1129662
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin induces ferroptosis in pancreatic cancer cells by inhibiting the Nrf2/GPX4 axis

Abstract: Pancreatic cancer is a common gastrointestinal tract malignancy. Currently, the therapeutic strategies for pancreatic cancers include surgery, radiotherapy, and chemotherapy; however, the surgical procedure is invasive, and the overall curative outcomes are poor. Furthermore, pancreatic cancers are usually asymptomatic during early stages and have a high degree of malignancy, along with a high rate of recurrence and metastasis, thereby increasing the risk of mortality. Studies have shown that ferroptosis regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…This modulation resulted in the accumulation of iron, overproduction of ROS, and cell death through ferroptosis [ 10 , 51 , 58 , 59 , 60 , 61 ]. Furthermore, amentoflavone [ 62 , 63 , 64 ], baicalin [ 54 , 55 , 65 ], erianin [ 37 , 41 , 57 , 66 , 67 ], gambogenic acid [ 68 ], auriculasin [ 69 ], wogonin [ 70 ], quercetin [ 71 , 72 ], shikonin [ 73 , 74 ], scoparone [ 75 ], osthole [ 76 ], also have shown to be able to inhibit cancer growth though the induction of ferroptosis. All of this suggests the potential for developing novel cancer treatments grounded in natural products acting as ferroptosis inducers.…”
Section: Resultsmentioning
confidence: 99%
“…This modulation resulted in the accumulation of iron, overproduction of ROS, and cell death through ferroptosis [ 10 , 51 , 58 , 59 , 60 , 61 ]. Furthermore, amentoflavone [ 62 , 63 , 64 ], baicalin [ 54 , 55 , 65 ], erianin [ 37 , 41 , 57 , 66 , 67 ], gambogenic acid [ 68 ], auriculasin [ 69 ], wogonin [ 70 ], quercetin [ 71 , 72 ], shikonin [ 73 , 74 ], scoparone [ 75 ], osthole [ 76 ], also have shown to be able to inhibit cancer growth though the induction of ferroptosis. All of this suggests the potential for developing novel cancer treatments grounded in natural products acting as ferroptosis inducers.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al have shown that by reducing NRF2 and increasing its targets (GPX4 and SLC7A11), WOG produces lipid peroxides, ROS, superoxides, excessive Fe 2+ , and also causes GSH deprivation. All of these processes lead to ferroptosis of different pancreatic cancer cell lines and decrease tumor growth in vivo and in vitro (Liu, Peng, et al, 2023).…”
Section: Flavonoids and Ferroptosis In Cancermentioning
confidence: 99%
“…Due to transcriptional regulation of GPX4 and SLC7A11 by NRF2, WOG can also induce ferroptosis in cancer cells.Liu et al have shown that by reducing NRF2 and increasing its targets (GPX4 and SLC7A11), WOG produces lipid peroxides, ROS, superoxides, excessive Fe 2+ , and also causes GSH deprivation. All of these processes lead to ferroptosis of different pancreatic cancer cell lines and decrease tumor growth in vivo and in vitro(Liu, Peng, et al, 2023).4.19 | 4,4 0 -Dimethoxychalcone 4,4 0 -Dimethoxychalcone (DMC) is a natural compound derived from flavonoids with antiaging properties by inducing autophagy(Carmona-Gutierrez et al, 2019). In addition, this flavonoid can induce ferroptosis in renal cell carcinoma and lung cancer cells through two mechanisms: First, DMC can upregulate NRF2 to enhance the expression of its target gene, HO-1.…”
mentioning
confidence: 99%
“…Further researches have shown that artemisinin and its derivatives can stimulate the ferroptosis cell pathway, containing down-regulating GPX4 expression, increasing ROS and intracellular iron production. There are some natural compounds defined as ferroptosis inducers, such as Ferroptoside ( Llabani et al, 2019 ), Erianin ( Luo and Xu, 2022 ) and Wogonin ( Liu et al, 2023a ). Ferrotocide, a diterpenoid natural product, is a thioredoxin inhibitor which inducs ferroptosis of breast cancer by inactivating thioredoxin (a cell antioxidant enzyme).…”
Section: Biological Compounds Intervene In Ferroptosis In Lung Cancermentioning
confidence: 99%